2017
DOI: 10.1111/1442-1984.12169
|View full text |Cite
|
Sign up to set email alerts
|

Nectary and gender‐biased nectar production in dichogamous Chamaenerion angustifolium (L.) Scop. (Onagraceae)

Abstract: In dichogamous plants, nectar characteristics (i.e. nectar amount and its composition) can differ between sexual phases. In the present study, we investigated the structural organization of the floral nectary, nectar production and carbohydrate composition in the protandrous Chamaenerion angustifolium (L.) Scop. (Onagraceae). The receptacular nectary consisted of an epidermis with numerous nectarostomata, several layers of photosynthetic secretory parenchyma, and subsecretory parenchyma. Nectariferous tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Floral nectar chemistry, including nectar carbohydrate composition, may differ significantly between populations, individuals, species or subspecies, or even between flowers on the same plant (e.g., Baker and Baker 1983b ; Galetto and Bernardello 2004 ; Petanidou 2005 ; Antoń and Denisow 2014 ; Antoń et al 2017 ). According to the classification of Baker and Baker ( 1983a ), the floral nectars of all Oenothera species are sucrose-dominant (the sucrose/(glucose + fructose) ratio being always above 6.5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Floral nectar chemistry, including nectar carbohydrate composition, may differ significantly between populations, individuals, species or subspecies, or even between flowers on the same plant (e.g., Baker and Baker 1983b ; Galetto and Bernardello 2004 ; Petanidou 2005 ; Antoń and Denisow 2014 ; Antoń et al 2017 ). According to the classification of Baker and Baker ( 1983a ), the floral nectars of all Oenothera species are sucrose-dominant (the sucrose/(glucose + fructose) ratio being always above 6.5).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with the previous results for other Onagraceae taxa, including Oenothera spp. (Stockhouse 1975 ; Nicolson and Thornburg 2007 ), demonstrating that predominance of sucrose in floral nectars occurs irrespective of flower morphology (but see Antoń et al 2017 ). Apparently, nectar carbohydrate composition in Oenothera is a more conservative feature than is flower morphology, suggesting that phylogenetic constraints may strongly influence nectar chemistry in that genus.…”
Section: Discussionmentioning
confidence: 99%
“…Nectar secretion was gathered using glass micropipettes [45,46]. Tulle isolators (mesh size <1 mm) were applied in the flower bud stage on randomly chosen individual inflorescences which remained bagged until nectar sampling.…”
Section: Nectar Productionmentioning
confidence: 99%
“…In the female phase, the participation of sucrose significantly decreased, whereas participation of both hexoses increased in comparison to the male phase. This could be caused by flower aging and consequent hydrolysis of sucrose into hexoses [ 19 , 41 , 42 , 43 ]. Gender-biased nectar composition could also be maintained by sexual selection or inbreeding avoidance, which is a common feature, especially for plants with dichogamous or heterostylous flowers [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies of nectar diversity have postulated that some nectar features, such as sugar and AA profiles, are species-invariant [ 7 , 9 , 10 , 11 ], and some new analyses support a rather conservative proportion of nectar components, that is sugars, between populations of the same species (e.g., [ 12 ]). However, this notion seems to be the result of technical difficulties associated with early analytical methods [ 3 , 13 ] because many recent studies have reported variation in nectar traits between populations, within populations, within one inflorescence, or even among sexual phases of the same flower [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Such variations are mainly a consequence of environmental factors, such as soil properties, air temperature, and sun exposure [ 1 , 2 , 8 , 13 , 21 ], and, according to the latest study, microorganisms inhabiting nectar [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%